MENGUNGKAP FAKTOR PSIKOLOGIS DI BALIK KECANDUAN JUDI ONLINE PADA DEWASA AWAL : STUDI KORELASIONAL - Widya Artha; Untung Subroto (STKIP Subang, 2026)
This study aims to analyze the relationship between decision making and online gambling addiction among young adults. The study used a quantitative approach with a correlational design. Data were collected through a Likert-scale questionnaire distributed to 200 respondents aged 18–25 years who had experience playing online gambling. The decision-making variable was measured based on the dimensions of Bounded Rationality theory, while online gambling addiction was measured based on the dimensions of non-substance addictive behavior. Data were analyzed using descriptive statistics and Spearman’s Rho correlation test, as the normality test indicated that the data were not normally distributed. The results showed a strong, negative, and significant relationship between decision making and online gambling addiction among young adults, with a correlation coefficient (ρ) of -0.680 and a significance value of 0.000 (p<0.05). These findings indicate that the better an individual’s decision-making ability, the lower their tendency toward online gambling addiction, and vice versa. Additional analyses showed that gender and age did not significantly differentiate decision-making ability or online gambling addiction. These findings reinforce the relevance of Bounded Rationality theory in explaining addictive behavior and provide a basis for developing prevention and intervention strategies for young adults vulnerable to online gambling.